Plant RNA binding proteins for control of RNA virus infection - Huh, Sung Un; Paek, Kyung-Hee (Frontiers in Physiology, 2013)
Plant RNA viruses have effective strategies to infect host plants through either direct or indirect interactions with various host proteins, thus suppressing the host immune system. When plant RNA viruses enter host cells exposed RNAs of viruses are recognized by the host immune system through processes such as siRNA-dependent silencing. Interestingly, some host RNA binding proteins have been involved in the inhibition of RNA virus replication, movement, and translation through RNA-specific binding. Host plants intensively use RNA binding proteins for defense against viral infections in nature. In this mini review, we will summarize the function of some host RNA binding proteins which act in a sequence-specific binding manner to the infecting virus RNA. It is important to understand how plants effectively suppresses RNA virus infections via RNA binding proteins, and this defense system can be potentially developed as a synthetic virus defense strategy for use in crop engineering.